AB0205 Comparison of thoracic hrct and self-reported questionnaires in the assessment of pulmonary involvement in rheumatoid arthritis patients: preliminary results. (12th June 2018) - Topcu, A.; Yalcınkaya, Y.; Karakurt, S.; Mursaloglu, H.H.; Albayrak, E.; Coşkun, N.; Demir, M.; Dalkılıc, E.; İnanç, N.
Abstract : Background: Pulmonary involvement in rheumatoid arthritis (RA) is one of the extra-articular manifestations affecting morbidity and mortality during the course of the disease. Pulmonary function tests (PFTs) and thoracic high-resolution computerised tomography (HRCT) are the standard of care in the assessment of pulmonary involvement in RA. In this study, we aimed to compare the findings between self-reported questionnaires and HRCT to detect pulmonary abnormalities in RA patients. Methods: Forty-two RA patients fulfilling ACR/EULAR classification criteria (2010) who had thoracic HRCT within 6 months of any symptom and/or any pathology on radiography of chest were included in the study. The patients were also assessed by modified Borg Scale, SF-36 Quality of Life Scale and Leicester Cough Questionnaire for the evaluation of respiratory symptoms. Results: Demographics and clinical characteristics were summarised in table 1. Warrick score, assessing the severity and extent of alveloitis and fibrosis on thoracic HRCT, was evaluated in 15 patients with ILD (score range:4–28). DLCO values were lower in patients with Warrick score ≥1 (73±22% vs. 88±12%, p=0.019) while FVC were not found to be different. The findings of HRCT and self-reported questionnaires were summarised in table 2. Any relationship between self-reported questionnaires and Warrick scores was not detected. Presence of any parenchymal lesions was found to be associated with SF-36 total score (p=0, 048). DLCO levels were found to be negatively correlated with SF-36 total scores (r=-0, 470, p=0, 006). Conclusions: In this study, we could not show any relationship between self-reported questionnaires and thoracic HRCT findings, except a weak association of the presence of parenchymal lesions with SF-36 scores. Alveolitis and/or fibrosis on thoracic HRCT were found to be associated with lower DLCO. DLCO was shown to be negatively correlated with SF-36 scores. SF-36 might be included in the detection of pulmonary evaluation in RA patients. The relationship between thoracic HRCT findings and self-reported questionnaires in RA necessitates further studies. Disclosure of Interest: None declared